(untitled) (Baghdad Science Journal, 2009)
This work represents the preparation of the starting material, 3-chloro-2-oxo-1,4-dithiacyclohexane (S) using a new method. This material was reacted with, 4-phenylthiosemicarbazide to give (H3NS3) as a tetradentate ligand H3L. New complex of rhenium (V) with this ligand of the formula [ReO(L)] was prepared. New complexes of the general formula [M(HL)] of this ligand when reacted with some metal ions where: M = Ni(II), Cu(II), Cd(II), Zn(II), Hg(II) have been reported. The ligand and the complexes were characterized by infrared, ultraviolet–visible, mass, 1H nuclear magnetic resonance and atomic absorption spectroscopic techniques and by (HPLC), elemental analysis, and electrical conductivity. The proposed structure for H3L with Re (V) is square pyramidal, while Ni(II) complex was square planar geometry, and with the rest of metal ions are distorted tetrahedral.